Intelligent Application Implementation Model for Automated Agent Negotiation - Hayder, Wrya Anwar; Husain, Mohammed Hassan (Kurdistan Journal of Applied Research, 2018)
In the last few years, multi-agents communication has seen an increased concern. The first main driver was an intelligent agent is claimed to be the next generation model for complex and distributed system engineering. Second the agents can automate process and communication on behalf of the agent’s users for proper actions and decisions. There are many concerns about how to implement communications among different agents in term of applied technology. In this paper we propose a REST- API and JSON technology as implementation tools that can be applied to implement intelligent web-based applications. REST is stands for Representational State Transfer which is allowing communication between web-based agents. JSON (JavaScript Object Notation) is a lightweight data format makes it easy for agents to parse and interchange data. This study has merged REST-AP and JSON technology into an automated negotiation model, and then a prototype is developed to successfully apply the proposed model. This model can facilitate application in business application negotiations and even internet of things (IOT) where HTTP protocol is used.